2021
DOI: 10.1136/bcr-2021-243520
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplastic internal carotid artery ending as an ophthalmic artery with multiple cerebral aneurysms, fenestrated Acom and triple A2

Abstract: A rare case of a hypoplastic internal carotid artery (ICA) terminating in the ophthalmic artery with multiple intracranial saccular aneurysms in the contralateral ICA, anterior communicating artery fenestration and triple A2 was identified. The aetiology and pathogenesis of ICA hypoplasia are subjected to certain hypotheses. Developing several collaterals to preserve the blood supply of the ipsilateral cerebral hemisphere could result in aneurysm formation due to flow overload on the contralateral vasculature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Other frequent presenting complaints were headache (six reports), 3,15,29,44,59,62 and seizure (four reports). 28,30,63,64 SAH (subarachnoid haemorrhage) due to a ruptured aneurysm was the cause of these symptoms in four reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other frequent presenting complaints were headache (six reports), 3,15,29,44,59,62 and seizure (four reports). 28,30,63,64 SAH (subarachnoid haemorrhage) due to a ruptured aneurysm was the cause of these symptoms in four reports.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggested a type that fitted best with their observations, and others noted that their cases had elements of more than one type. 39,40,59,60…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation